Substitutes or Complements? Diagnosis and Treatment with non-Conventional and Conventional Medicine - Aida Isabel Tavares (Kerman University of Medical Sciences, 2015)
Background Portugal has a strong tradition of conventional western healthcare. So it provides a natural case study for the relationship between Complementary/Alternative Medicine (CAM) and Western Medicine (WM). This work aims to test the relationship between CAM and WM users in the diagnosis and treatment stages and to estimate the determinants of CAM choice. Methods The forth Portuguese National Health Survey is employed to estimate two single probit models and obtain the correlation between the consumption of CAM and WM medicines in the diagnosis and treatment stages. Results Firstly, both in the diagnosis and the treatment stage, CAM and WM are seen to be complementary choices for individuals. Secondly, self-medication also shows complementarity with the choice of CAM treatment. Thirdly, education has a non-linear relationship with the choice of CAM. Finally, working status, age, smoking and chronic disease are determinant factors in the decision to use CAM. Conclusion The results of this work are relevant to health policy-makers and for insurance companies. Patients need freedom of choice and, for the sake of safety and efficacy of treatment, WM and CAM healthcare ought to be provided in a joint and integrated health system.